1997
DOI: 10.1097/00005392-199705000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless Percutaneous Renal Surgery

Abstract: Tubeless percutaneous renal surgery is a safe procedure and offers numerous advantages over routine placement of a nephrostomy tube. The hospitalization, analgesia requirements, return to normal activities as well as cost are significantly less with this new technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 8 publications
2
53
1
1
Order By: Relevance
“…It has been shown that using a small-caliber nephrostomy tube, a miniperc, an internal stent, and tubeless PCNL can decrease postoperative pain and the length of the hospital stay. [3] The term "tubeless percutaneous nephrolithotomy" was first used by Bellman et al [4] . The tubeless PCNL involves internalization of the postoperative renal drainage by placement of an internal stent (either ureteric or JJ catheter) and bladder catheter instead of the traditional nephrostomy tube.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that using a small-caliber nephrostomy tube, a miniperc, an internal stent, and tubeless PCNL can decrease postoperative pain and the length of the hospital stay. [3] The term "tubeless percutaneous nephrolithotomy" was first used by Bellman et al [4] . The tubeless PCNL involves internalization of the postoperative renal drainage by placement of an internal stent (either ureteric or JJ catheter) and bladder catheter instead of the traditional nephrostomy tube.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers opted for a ‘totally tubeless’ approach and as such our analysis is subcategorised into three elements: (1) standard PCNL (tubed). (2) Tubeless with a ureteric stent: in 11 articles, standard PCNL groups were compared to groups whereby drainage was provided by ureteric stents [2,3,4,5,7,9,10,12,18,19,20]. Within this category, 2 studies included three groups: two calibres of nephrostomy (large-bore and small-bore) compared with ureteric stents [3,5].…”
Section: Resultsmentioning
confidence: 99%
“…PCNL is now the operation of choice for the management of large, complex renal calculi [2,3,4,5,6,7]. Historically temporary nephrostomy tubes of varying calibre and type have been left in place at the end of PCNL procedures for several reasons: drainage, tamponade of bleeding and to permit second-look procedures [1,2,3,8,9,10,11]. There is an ever-growing literature base documenting numerous technological and procedural refinements to this approach, such as the use of smaller calibre nephrostomies [4,5,6,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations